Ultrasound homogenization of milk cream at low temperature - Fithri Choirun Nisa; Fan Zhu; Conrad Perera; Liurong Huang; Yacine Hemar (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Ultrasonication has been identified as a particularly promising technology for homogenization of dairy products. Homogenization of cream, by reducing fat globule size, can be utilized to inhibit creaming. The homogenization of cream usually leads to increased viscosity. Cream with fat level greater than 17% cannot be homogenized with satisfactory results since conventional homogenization methods cause coalescence and mostly agglomeration. The aim of this study was to investigate the influence of ultrasonication on milk cream (5-30% fat) and to study the phenomenon of formation of fat clusters during sonication (0.5-15 mins) at low temperature (2°C). The results showed that ultrasonication can reduce the fat globule size, although it resulted in the formation of fat clusters at short time (<1min), but at longer time, fat clusters can be broken. On the other hand, ultrasound homogenization tends to increase the viscosity of cream at various fat contents. Microstructure of solid phase showed that there was formation of double emulsions and partial fat coalescence. Ultrasound homogenization with the addition of SDS as small-molecule surfactant can prevent the formation of fat clusters. Fatty acid composition in solid phase shows that it consists of long-chain fatty acids in higher amount compared to that present in the liquid fraction. Whereas the concentration of short and medium chain fatty acids in the liquid phase was higher compared to that in solid phase. The utilization and optimization of ultrasound for cream homogenization has a potency to solve the limitation of conventional method (pressure homogenizer) which commonly used in dairy industry.